Synthesis and antioxidant properties of 8-aminoderivatives of 7-(2-hydroxy-2-phenylethyl)-teophylline - Turpak, M. S. (Запорізький державний медичний університет, 2019)
Recently, there is a strong interest in determining the antioxidant activity of medicinal forms and biologically active substances. Due to the harmful effects of free radicals, walls of vessels and membranes become damaged, lipids are oxidized, resulting in serious pathological changes, cardiovascular and cancerous diseases. The harmful effect of "free radicals" on the body may be reduced by the use of some drugs, biologically active substances that have high antioxidant activity. Therefore, the problem of antioxidant search is perspective and relevant. The aim of this work is to develop simple laboratory methods for the synthesis of unpublished in the literature 7,8-disubstituted of theophylline and the study of their physical-chemical and biological properties.
Keywords: тези доповідей